Improving Education Outcomes in South Asia : Findings from a Decade of Impact Evaluations - Asim, Salman (World Bank, Washington, DC, 2015)
There have been many initiatives to improve education outcomes in South Asia. Still, outcomes remain stubbornly resistant to improvements, at least when considered across the region. To collect and synthesize the insights about what actually works to improve learning and other education outcomes, this paper conducts a systematic review and meta-analysis of 29 education-focused impact evaluations from South Asia, establishing a standard that includes randomized control trials and quasi-experimental designs. It finds that while there are impacts from interventions that seek to increase the demand for education in households and communities, those targeting teachers or schools and thus the supply-side of the education sector are generally much more adept at improving learning outcomes. In addition, interventions that provide different actors with resources and those that incentivize behavioral changes show moderate but statistically significant impacts on student learning. A mix of input- and incentive-oriented interventions tailored to the specific conditions on the ground appears most promising for fostering education outcomes in South Asia.